DIFFERENCE IN THE TREATMENT EFFECTIVENESS OF WOODWORKING WASTEWATER BETWEEN POLYALUMINIUM CHLORIDE-BASED COAGULANTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
in the work, a comparative study of the efficiency of coagulation of a model solution, simulating woodworking wastewater, with the known composition of polyaluminium chloride (РАС) with aluminium sulphate and a new РАС-based composite coagulant was carried out. It has been found that, in comparison with the known composition, the developed composite coagulant makes it possible to enhance the efficiency of the wastewater treatment and to decrease the content of residual aluminium therein, which enables the return of the treated water in the technological cycle. The enhancement of the coagulation ability of the developed composite coagulant relative to the known composition of РАС with aluminium sulphate is governed by the formation, in the AlCl3/РАС system, of polynuclear Аl-complexes with a high-molecular structure. This is testified by the results of the comparative study of those coagulants by the Ferron and ion mass spectroscopy methods.